2009
DOI: 10.1089/zeb.2008.0555
|View full text |Cite
|
Sign up to set email alerts
|

A Primer for Morpholino Use in Zebrafish

Abstract: Morpholino oligonucleotides are the most common anti-sense “knockdown” technique used in zebrafish (Danio rerio). This review discusses common practices for the design, preparation, and deployment of morpholinos in this vertebrate model system. Off-targeting effects of morpholinos are discussed as well as method to minimize this potentially confounding variable via co-injection of a tP53-targeting morpholino. Finally, new uses of morpholinos are summarized and contextualized with respect to the complementary, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
294
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 397 publications
(301 citation statements)
references
References 49 publications
3
294
0
4
Order By: Relevance
“…S4). As the translation-blocking effects of MOs generally wear off within 4-5 d after injection, 32 these data suggest that autophagy during the first 4-5 d of development is essential for long-term fish viability.…”
Section: Autophagy Gene Knockdown Results In Increased Numbers Of Deamentioning
confidence: 73%
“…S4). As the translation-blocking effects of MOs generally wear off within 4-5 d after injection, 32 these data suggest that autophagy during the first 4-5 d of development is essential for long-term fish viability.…”
Section: Autophagy Gene Knockdown Results In Increased Numbers Of Deamentioning
confidence: 73%
“…45 Not surprisingly, PMOs have also proven to be effective anti-miRNA compounds in Zebrafish. Flynt et al 46 reported knockdown of miR-214 in Zebrafish, demonstrating a role for this miRNA in muscle cell development.…”
Section: Inhibiting Mirna Function With Synthetic Oligonucleotides Dementioning
confidence: 99%
“…NudC MO-1 (5′-TCTTTCGTCATCGTCACCCATTTTC-3′) targeted part of the open reading frame of zebrafish NudC mRNA, the rescue construct was engineered to change the nucleotide sequence without altering the encoded protein. As NudC MO-2, cofilin 1 MO-1 and MO-2 separately target the 5′-UTR sequence of NudC and cofilin 1 mRNA, the open reading frames of these two genes were simply cloned into pCS107 vector for rescue experiments [43]. Capped and polyadenylated RNAs were synthesized with the SP6 mMessage mMachine kit (Ambion).…”
Section: Plasmids and Oligonucleotidesmentioning
confidence: 99%